The Role of Self-Efficacy in Mediating Entrepreneurial Alertness and Skill Development in Secondary Schools - Ekwutosi Ozioma Chukwu; Amos Nnaemeka Amedu (Universitas Negeri Semarang, 2025)
This study examined the mediating effect of students' self-efficacy on the relationship between entrepreneurial alertness (EA) and entrepreneurial skill development (ESD). This study employed a correlational survey research design to establish the relationship among the variables. The population of the study is 3423 senior secondary students in Enugu State. The sample size is 379 students. Participants were purposely selected. The data were collected using the Entrepreneurial Alertness Questionnaire for Senior Secondary Students (EQS). The questionnaire's reliability was assessed using the Cronbach alpha and an overall reliability coefficient of 0.96 was obtained. Survey data were entered into SPSS and transferred to WarpPLS version 7.0 for analysis. Path analysis was used because it presents the network graphical relationship among variables. The path diagram and coefficients were utilized to answer the research questions, and the hypothesis was tested at a significance level of 0.05. There was a strong positive relationship between entrepreneurial alertness and skill development (β = 0.36; P=0.01) among senior secondary students. Students' self-efficacy was a significant mediator between entrepreneurial alertness and skill development which led to a 54% (r2 =54) variation in students’ entrepreneurship skills. This study concludes that students' self-efficacy significantly moderates the relationship between entrepreneurial alertness and skill development among secondary school students. Enhancing students' self-efficacy has both direct and indirect positive effects on their entrepreneurial skills development. Since self-efficacy significantly mediates the relationship between EA and ESD, educational administrators and teachers should ensure that instructional approaches stimulate secondary school students’ self-efficacy.